Smart Drug Delivery System (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The objective of this study is to explore the concept of smart drug delivery systems and their role in improving the effectiveness, safety, and precision of therapeutic treatments. These systems are designed to deliver drugs to specific target sites while minimizing side effects and enhancing patient compliance. Methodology: A review of recent literature was conducted to examine various smart drug delivery technologies, including nanoparticles, liposomes, hydrogels, polymeric carriers, and stimuli-responsive systems. The analysis focused on their mechanisms of controlled drug release, targeting strategies, and applications in the treatment of chronic diseases such as cancer, diabetes, and cardiovascular disorders. Conclusion: Smart drug delivery systems represent a significant advancement over conventional drug administration methods by enabling controlled, targeted, and sustained drug release. These technologies improve therapeutic efficacy, reduce toxicity, and support personalized medicine. Despite challenges related to manufacturing complexity, cost, and regulatory approval, ongoing research and technological innovations continue to enhance their clinical potential. Smart drug delivery systems are expected to play an increasingly important role in modern healthcare by providing safer, more efficient, and patient-centered treatment options.
Keywords: nanoparticles; liposomes; hydrogels; polymeric carriers; stimuli-responsive systems